MALAY LANGUAGE LEARNING STRATEGIES AMONG INTERNATIONAL STUDENTS BASED ON FOUR SKILLS - Sharala Subramaniam (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Bahasa Melayu (BM) is the main language in Malaysia. BM is a prerequisite for international students to graduate and awarded a diploma or degree. In this case, International students will face various other problems in mastering the listening, reading, speaking and writing skills within such a short period. Among those often discussed are that a majority of the international students taking BM courses in universities face various problems and are weak in acquiring the language skills taught to them within such a short period. This directly affects their studies and academic achievement as a whole. The aim of this study was to help facilitate the international students to learn BM in terms of the four skills. These skills are Listening, Speaking, Reading, and Writing. This study has been successfully identify language learning strategies based on four skills for international students in Higher Educational Institutions in Malaysia.